Fat Supplementation of Human Milk with MCT Oil for Promoting Weight Gain in Preterm Infants - Nagham Nawaz Awan, Amna Mateen, Syeda Shireen Gul, Sana Razzak, Adeela Riaz, Saira Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The addition of medium chain triglycerides is preferable as they are more easily digested and quickly absorb in bloodstream than long chain fat and provide ready supply of energy by increasing fatty acid bioavailability. Modular products like micro lipids and medium-chain triglyceride (MCT) oils are now focused as a fat supplementation. The rate of weight gain with MCT is not well known, and there is very less research done in Pakistan. Objective: To determine the effect of MCT oil supplemented human milk compared with un supplemented human milk fed to preterm infants on promoting weight gain. Study Design: Randomized controlled trial Study Setting: This study was conducted in Department of Neonatology, Children Hospital, PIMS, Islamabad, Pakistan from 20th August 2022 to 20th February 2023. Methodology: The study conducted after approval from institutional ethical committee. A total of 160 preterm infants fulfilling the inclusion criteria and enrolled in the study after informed consent from parents. The patients were receiving enteral feeding of human milk within neonatology department of hospital was included and they were randomly assigned to Group NF (receiving 20 ml of human milk without MCT oil), Group F (receiving 20ml of human milk with 1 ml of MCT oil fat). Primary outcomes were including growth in term of weight gain at measured at 1st ,5th and 10th day of MCT oil intake after hospital admission. Secondary outcome included feeding intolerance, diarrhoea, sepsis and necrotising enterocolitis. All the data was collected in the form of a questionnaire. The statistical analysis was done by using SPSS version 20. Results: One sixty very low birth weight infants were analyzed in this study. All infants were randomly divided into two groups: F and NF, the demographic details. The weight of infants was measured on first day, fifth day and tenth day and noted that the frequency of infants improved the weight gain after taking human milk without fat supplementation or human milk with fat supplementation. We found the gradually infants more increasing their weights in Group F as compared to Group NF. On tenth day 75% infants reaches between1400-1490 gm weight (p<0.001). The average daily gain in weight of Group F infants (g/kg). 12.2 Group A, 13.6 in group B were calculated on day first. The average daily weight was shifted in Group B from 13.6 to 14.9 on day fifth then it was further increased as 15.6 in Group C, and 15.8 in Group D. Practical Implication: The fat in the milk of humans is a significant source of energy. In an underdeveloped State like Pakistan that is short on resources, (MCT) oil can be a useful substitute for MCT due to its high MCT content. Few research studies have been conducted into this area thus far. Previous studies have had a low number of participants and produced contradictory findings. Therefore, this study was carried out to compare the efficacy of feeding preterm infants human milk supplemented with MCT oil to that of feeding them human milk without the supplement. Conclusion: Our study shows the average weight gain in those infants fed fat supplementation of MCT oil added in breast milk. The study provides data regarding the selection and use of fat supplemented human milk over non-supplemented human milk and this reduces the morbidity and mortality rate due to insufficiency of nutrients. Keyword: Fat supplementation, MCT oil, breast milk, preterm infants, weight gain rate.